2021
DOI: 10.1080/09500693.2020.1865588
|View full text |Cite
|
Sign up to set email alerts
|

What do they know? Investigating students’ ability to analyse experimental data in secondary physics education

Abstract: This paper explores students' ability to analyse andinterpret empirical data as inadequate data analysis skills and understandings may contribute to the renowned disappointing outcomes of practical work in secondary school physics. Selected competences, derived from a collection of leading curricula, are explored through interviews and practical tasks, each consisting of three probes. The 51 students, aged 15 and commencing post-compulsory science education in the Netherlands, were able to carry out basic skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 39 publications
(67 reference statements)
0
10
0
3
Order By: Relevance
“…Students lack the ability to structure a paper and lack skills in referencing, use of captions and formatting. Despite the fact that students are able to draw adequate graphs on paper (Pols et al, 2021), displaying graphs digitally remains difficult. Similar to Sadikin et al's (2021) findings, many students were found to have insufficient experience with using spreadsheets, e.g., in processing data, axis labelling, drawing of a trendline, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students lack the ability to structure a paper and lack skills in referencing, use of captions and formatting. Despite the fact that students are able to draw adequate graphs on paper (Pols et al, 2021), displaying graphs digitally remains difficult. Similar to Sadikin et al's (2021) findings, many students were found to have insufficient experience with using spreadsheets, e.g., in processing data, axis labelling, drawing of a trendline, etc.…”
Section: Discussionmentioning
confidence: 99%
“…To give just one example, one of the most important research skills for STEM students is constructing a graph out of a dataset. A recent study in science education shows that pre-university physics students are generally able to construct suitable graphs on paper, 67% of which meet all scientific conventions (Pols et al, 2021). However, when students are confronted with constructing similar graphs by digital means, the results are insufficient (Sadikin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As students ultimately should be able to apply in an integrated way the full scope of PACKS and make research decisions themselves [4,9,10], the students engage in a final project where they conduct a self-conceived experiment [11]. Students' ability to conceive and conduct a physics experiment as well as report on it, is assessed using a grading rubric that is derived from the Assessment Rubric for Physics Inquiry (ARPI) [12].…”
Section: Background Of the Coursementioning
confidence: 99%
“…As an educator, the teacher tries to find out how students think about physics (Suwonjandee et al, 2018;Pols et al, 2021). There are several possibilities that make students think that physics is uninteresting.…”
Section: Introductionmentioning
confidence: 99%